Analisis Pendapatan dan Kelayakan Usahatani Jeruk Manis Di Nagari Taruang-Taruang Rao Kabupaten Pasaman - Andika, Muhammad Atri; Safitri, Sri Ariani (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
The management of orange farming in Nagari Taruang-Taruang Rao, Pasaman Regency, aims to increase production and farmer income. By increasing the production, the profit or income of farmers will be maximized. This study was conducted to analyze the income of sweet orange farming in Nagari Taruang-Taruang Rao, Pasaman Regency. This study was conducted as a quantitative research with an analysis form, and the subjects used as sources in this study were sweet orange farmers. The data analysis method uses the income and feasibility formula. Sweet orange farming is feasible to be cultivated in the research area because the R/C Ratio value obtained is greater than one (R/C Ratio 1). With a value of 5.88 1 and the B/C Ratio value obtained is greater than one (B/C Ratio 1). With a value of 5.17 1, it is said that sweet orange farming is feasible to be cultivated in Nagari Taruang-Taruang Rao, Pasaman Regency.